STRATEGI KOMUNIKASI DALAM MENGIMPLEMENTASIKAN PERATURAN GUBERNUR NOMOR 141 TAHUN 2016 TENTANG KARTU JAKARTA PINTAR - GAN GAN GIANTIKA (Jurnal Komunikasi, 2016)
Jakarta is the capital city of Indonesia continues to be reflected for other regions in developing all aspects, one of which is education. The government through the Governor Decree Number 141 Year 2016 set rules on Personal Cost Assistance Education for Students From Disadvantaged Families Through Jakarta Smart Card. The purpose of this study to determine the Communication Strategy In implementing the Governor Regulation Number 141 2016 About Jakarta Smart Card in SDN 01 Pagi Tebet Barat, South Jakarta. This study used a qualitative approach. The data collection is done with the interview as the primary data. While secondary data obtained from the literature and electronic media. Based on the research that Tebet Barat SDN 01 Pagi perform communication strategies in implementing the Governor Regulation No. 141 Year 2016. In this communication strategy Tebet Barat SDN 01 Pagi perform such communication strategies, objectives, disposition and bureaucratic structure. So that the implementation of Governor Regulation Number 141 Year 2016 can be realized.  Keywords: Communication Strategies, Implementation, Jakarta Smart Card